Energy analysis of secondary droplet atomization schemes; International Communications in Heat and Mass Transfer; Vol. 117 - Antonov D. V. Dmitry Vladimirovich; Shlegel N. E. Nikita Evgenjevich; Strizhak P. A. Pavel Alexandrovich; Tarlet D. Dominique; Bellettre J. Jerome (2020, 2020)
Title screen